Cortisol and its metabolites in juvenile Siberian sturgeon, Acipenser baerii Brandt, 1869 in response to short-term food deprivation - Ashouri, G.; Yavari, V.; Bahmani, M.; Yazdani, M. A.; Kazemi, R.; Morshedi, V.; Eslamlo, K. (2014)
In this study, the effect of short-terms starvation (0, 2, 4 and 8 days) on plasma cortisol, glucose, triglyceride and cholesterol levels and also hepatosomatic index in Siberian sturgeon, Acipenser baerii, was investigated. After acclimation to experimental conditions for 10 days using formulated diet, 180 juvenile Siberian sturgeons (mean weight ± S.E.=19.3±0.4, n=15) were randomly distributed among twelve circular, 500l, fiber glass holding tanks with a flow-through system. In this study, control fish (C) were fed with formulated diet to apparent satiation four times daily throughout the experiment. The other three groups were deprived from feed for 2 (T1), 4 (T2) and 8 (T3) days, respectively. Blood samples were taken at the end of the starvation periods for biochemical analyses. Plasma cortisol, triglyceride and cholesterol levels were not significantly different between control and starved fish at the end of the food deprivation periods, but plasma glucose levels were significantly lower in the starved groups, compared to the control fish. HSI index significantly decreased in all starvation groups, except T1, in comparison to the control. The results suggest that energy reserves mobilization during starvation in Siberian sturgeon may be achieved without the involvement of cortisol. Moreover, in this species there are clear indications of metabolic adjustment ability to short periods of food deprivation. Published